Understanding the molecular mechanism of thio-Claisen rearrangement of allyl phenyl sulfide and allyl vinyl sulfide using bonding evolution theory coupled with NCI analysis. (4th July 2018) - Nouri, Arezu; Zahedi, Ehsan; Ehsani, Morteza; Nouri, Azita; Balali, Ebrahim
ABSTRACT: A joint application of bonding evolution theory (BET) and non-covalent interaction (NCI) analysis provides a powerful tool to explain the molecular mechanism of organic reactions. Thio-Claisen rearrangements (TCR) of allyl phenyl sulfide and allyl vinyl sulfide have been studied energetically using the MPWB1K/6-311G(2 d, d, p ), M06-2x/6-311G(2 d, d, p ) and the complete basis set model chemistry CBS-QB3 to predict activation barriers and thermodynamic parameters. Loss of aromaticity within the benzene ring along the TCR of allyl phenyl sulfide leads to a higher activation barrier and its endergonicity (endothermicity) nature, while TCR of allyl vinyl sulfide is an exergonic (exothermic) rearrangement with lower activation barrier. The molecular mechanisms are described by using MPWB1K/6-311G(2 d, d, p ) wavefunctions and energy profiles. The TCR of allyl phenyl sulfide and allyl vinyl sulfide can be described by the sequence of catastrophes 6-[C † C]F[F † F † F] TS [C † C]C † -0 and 8-C † CC[F † F † F] TS FCC † -0, respectively, by the following chemical events: (a) homolytic bond breaking of C−S single bond and formation of pseudoradical centers on the atoms; (b) annihilation of the pseudoradical centers and reorganization in covalent bonds; (c) appearance of the pseudoradical centers on the terminal carbon atoms; (d) formation of new C−C single bond by the C-to-C coupling of pseudoradical centers when the TS of the reaction is reached and left behind. NCI isosurface appears in the region of broken C−S bond and forming C−C bond where the monosynaptic basins were localized. GRAPHICAL ABSTRACT: